The Use of Mobile Applications Such As Duolingo to Support Self-directed English Learning - Dhiyaushshafa, Dendeu Najla; Otong Setiawan Djuharie (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examined the role of mobile-based language learning applications, particularly Duolingo, in supporting self-directed English language learning. Using a qualitative approach through literature review, this research analyzed various academic studies published between 2018 and 2024 that focused on the effectiveness of Duolingo in improving vocabulary, grammar, and learning motivation. The results indicated that Duolingo helped learners develop consistent study habits and fostered autonomy through its gamified features. In addition, the app offered a flexible and engaging learning environment. However, limitations were found in speaking skill development and social interaction, which the application did not fully support. Overall, Duolingo serves as a useful supplementary tool in learning English, but it should be combined with other methods for more comprehensive outcomes.